ACUTE PANCREATITIS ASSESSED WITH COMPUTED TOMOGRAPHY USING A MODIFIED COMPUTED TOMOGRAPHY SEVERITY SCORE: A PROSPECTIVE STUDY. - Kumari, Manisha; Singh, Sumity; Vaibhav, Waghmare; Kumar, Rahul (Student’s Journal of Health Research Africa, 2024)
Introduction The analysis of the seriousness of acute pancreatitis has a noteworthy part in treatment. Moderate pancreatitis can be managed by medicines, but severe pancreatitis needs thorough observation and specific treatment. The present research aims to evaluate the relation with patient result changeability of a modified CT severity score for the examination of subjects with acute pancreatitis with the present CT severity index. Materials and Methods This is prospective research carried out at Indira Gandhi Institute of Medical Sciences, Patna, Bihar, India, in which 50 patients were included for 6 months. All the detailed history of the patients was recorded. Scans were performed utilizing GE bright speed 16-slice computed tomography. The bolus tracking technique was utilized for a distinctive scan by placing the tracker in the aorta. Results 29 subjects were males, and 21 subjects were females. The major cause of acute pancreatitis is alcohol intake. Acute pancreatitis in 33 patients was caused by the intake of alcohol. 13 had acute pancreatitis caused by bile stones. 3 patients with acute pancreatitis had idiopathic causes. 1 patient had other causes. In 11 patients’ cardiovascular system is involved. In 15 patients, the respiratory system was involved and in 24 cases the renal system was involved. Conclusion A modified tomography scan is a great method for the examination of acute pancreatitis. It aids in the detection of pancreatic necrosis and localized complications. In the current analysis, no remarkable interconnection was seen with the requirement of operative procedure Recommendation Modified computed tomography can be used in the evaluation of the severity of acute pancreatitis. It even helps in the detection of the requirement of surgical intervention.